Comparison of Growth Diagrams Of Indonesian Children to 2006 World Health Organization Growth Standards in diagnosing stunting - Rizki Aryo Wicaksono; Karina Sugih Arto; Rina Amalia Karomina Saragih; Melda Deliana; Munar Lubis; Jose Rizal Latief Batubara (Indonesian Pediatric Society, 2020)
Background Stunting represents a linear growth disturbance due to chronic malnutrition, recurrent infection, and inadequate psychosocial stimulation. The 2006 World Health Organization (WHO) Growth Standards are utilized as a modality in monitoring children's growth, but to date, there has been no recommendation on use of the Growth Diagrams of Indonesian Children to monitor the growth of Indonesian children. Objective To determine the proportion of stunting, the sensitivity and specificity of Growth Diagrams of Indonesian Children for diagnosing stunting. In addition, we aimed to compare proportions of stunting using the 2006 WHO Growth Standards and Growth Diagrams of Indonesian Children. Method A cross-sectional study was conducted in Lawe Alas District, Southeast Aceh, Indonesia, from December 2017 to May 2018. Subjects were children aged 1-59 months who fulfilled the inclusion criteria. Subjects were obtained using a consecutive sampling method. Weight and height measurements were plotted on the Growth Diagrams of Indonesian Children and on the 2006 WHO Growth Standards to determine the stature o subjects. Stunting was defined as the index Z-score for HAZ of less than -2 SD for the 2006 WHO Growth Standards, and an HAZ index of below the 10th percentile (p10th) for the Growth Diagrams of Indonesian Children. Results Of 141 subjects, 66 (46.8%) had stunting based on the 2006 WHO Growth Standards and 51 (34.8%) had stunting based on Growth Diagrams of Indonesian Children. The sensitivity and specificity of the Growth Diagrams of Indonesian Children were 75.5% and 98.66%, respectively. Significantly more children were considered to be stunted using the 2006 WHO Growth Standards than using the Growth Diagrams of Indonesian Children. Conclusion Stunting prevalence is high in Southeast Aceh. The Growth Diagrams of Indonesian Children is a spesific and sensitive tool to diagnosed stunting in accordance with Indonesian children's growth patterns.